Geometric Sequences

Algebra Level 1

A geometric sequence has t 2 = 6 t_2 = -6 and t 5 = 162 t_5 = 162 . Find its general term t n t_n .

t 2 = t_2 = second term; t 5 = t_5 = fifth term; t n = t_n = nth term;

2*(3)^n 2*(-3)^(n-1) 3(-4)^n 6n

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hung Woei Neoh
Jun 19, 2016

Let the first term be a a and the common difference be r r . The n n -th term of the progression is given as

t n = a r n 1 t_n = ar^{n-1}

Now, we know that

t 2 = a r = 6 t 5 = a r 4 = 162 t_2 = ar = -6\\ t_5 = ar^4 = 162

Now, we divide these two equations:

t 5 t 2 = a r 4 a r = 162 6 r 3 = 27 r = 3 \dfrac{t_5}{t_2} = \dfrac{ar^4}{ar} = \dfrac{162}{-6}\\ \implies r^3 = -27\\ r=-3

Then,

a ( 3 ) = 6 a = 2 a(-3) = -6\\ a=2

Therefore, t n = 2 ( 3 ) n 1 t_n = \boxed{2(-3)^{n-1}}

Abdullah Mughal
Jun 18, 2016

t 2 = t 1 ( r ) t2 = t1(r) ------ (1)

t 5 = t 1 ( r 4 ) t5 = t1(r^4) ------ (2)

[ t 1 ( r 4 ) ] / [ t 1 ( r ) ] = 162 / 6 [t1(r^4)]/[t1(r)] = 162/-6 ------ (2) / (1)

r 3 = 27 r^3 = -27

r = -3

t1(-3) = -6

t1 = 2

t n = 2 ( 3 ) n 1 tn = 2*(-3)^{n-1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...